The Government Responsibility in Providing Legal Protection to The Public against The Distribution of Unhealthy Food - Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2026)
Ultra-processed food products, also known as UPF, have become a daily staple in Indonesians. UPF contains high levels of sugar, salt, and fat, which can lead to obesity and diabetes in those of productive age. Food safety regulations lack an effective regulatory system to curb the high consumption of UPF. Specifically, Minister of Health Regulation No. 63 of 2015 regulates the Use of Sugar, Salt, and Fat. However, its implementation has been hampered by industry resistance, which considers this policy to be a hindrance to business growth. This research, using a juridical-normative approach, examines various relevant laws and regulations, such as the Consumer Protection Law, the Food Law, and their derivative regulations. This research uses a juridical-normative approach by examining various related laws and regulations, such as the Consumer Protection Law, the Food Law, and their derivative regulations. The type of research used is descriptive-analytical, which is aiming to describe systematically and factually the effectiveness of regulations and the factors that influence the success of their implementation. This research uses secondary data. Secondary data consists of the results of literature studies, legal documents, and reports from related institutions, such as WHO and Indonesian Food and Drug Authority. This combination of data sources provides a strong foundation for conducting a comprehensive analysis of the problem being studied. Food safety is an essential requirement for all Indonesians to consume. The government have a crucial role in maintaining the diversity of culinary culture while still prioritizing balanced nutritional standards to ensure the health and safety of food products consumed by the public. Various government interventions to reduce the consumption of unhealthy foods include the need for regulations governing UPF, fast food excise, restrictions on UPF advertising, and the need for supervision and guidance for school vendors regarding food and beverages sold to schoolchildren. Existing regulations, such as the Food Law and the Minister of Health Regulation, are not yet fully adequate in protecting consumers from the dangers of excessive consumption of products containing sugar, salt, and fat. The government plays a crucial role in ensuring that producers comply with the obligation to include nutritional information and health messages on food products.